Efikasi Mengajar Sebagai Mediator Peranan Faktor Kepribadian terhadap Performasi Mengajar Guru - Rochman Hadjam, M. Noor; Widhiarso, Wahyu (Universitas Ahmad Dahlan, 2011)
AbstractThe aim of this study is to test the role of teaching efficacy as a mediatorrelationship between personality factors and optimal teaching performance.Construct personality factor involved is Big Five personality. Participantsin this study were 142 teachers who are representatives of the provincesin Indonesia. Measurement instruments are Five Factors Personality Scale,Teaching Efficacy Scale and Teaching Performance Scale. This studysuggest that the role of personality factors indirectly effect is better to explainvariations in teaching performance than directly effect. This conclusionsare based on two results of the statistical analysis: (1) results fromhierarchical regression analysis indicates that at final stage, entering factorsof teaching efficacy has reduced the role of all five factors of personality tothe teaching performance of teachers ( F = 17.81 p<0.01; R2 = 21.8%).Comparison of coefficient value from two types of effect (direct effectversus indirect effect) in structural equation modeling (SEM), suggest thatthe indirect effect coefficient more significant than direct effect. In general,our findings suggest that construct personality has a broad scope that requireother construct more specific or narrower trait as a mediator in explainingthe behavior of the criteria.